Petrology and geochemistry of the Middle Pennsylvanian (Langsettian) Clintwood coalbed, Pike County, Kentucky - James C. Hower; Cortland F. Eble; Shelley D. Hopps; Tonya D. Morgan; Vivian A. Edwards (International Journal of Coal Science & Technology)
Abstract The Middle Pennsylvanian, Langsettian sub-stage Clintwood coal, along with its correlatives, was one of the more important energy resources in eastern Kentucky. The coal thickens from the NE-SW-trending Belfry anticline in central Pike County to the southeast, towards the Virginia-Kentucky border. Much of the thickness increase is in the bright lithotypes below a dull lithology. The bright lithologies transition from a bright clarain + vitrain + fusain lithology to a clarain + fusain lithology to the southeast. Half of the lithotypes in the three analyzed sections exceed 1000-µg/g Rare earth elements + Y + Sc (REYSc) (ash basis). The LaN/SmN vs. GdN/YbN and LaN/SmN vs. CeN/CeN * plots suggest that the top lithotype may have had best indication of an oxidizing environment. Positive GdN/GdN* and EuN/EuN * in some of the lithologies suggests that there may have been a hydrothermal influence in the sediment sources and/or in the diagenesis of the coal. Consideration of LaN/SmN and Zr (µg/g; ash basis), Zr vs. Sr, and V/Cr vs. inertinite/(inertinite + vitrinite) indicates that the dull lithotypes existed in a distinct geochemical environment compared to the brighter lithotypes. The isolation of the dull lithotypes from the bright lithotypes is supported by principal components analysis on inertinite/(inertinite + vitrinite), LaN/SmN, V/Cr, Sr, and either Zr or Ln(100(TiO2)/Al2O3).